(untitled) (Archive of Conferences, 2021)
Currently, Uzbekistan is actively updating the literary Uzbek language due to the revival of national and cultural values in the spiritual life of people. There are changes in the language situation of the country, the role of the state and interethnic languages at the official level is increasingly strengthened, while the socio-political significance and comprehension of the AngloUzbek language interaction have faded into the background, although these two languages are closely and universally in contact at different language levels due to the social and economic relations between representatives of various segments of society that have developed in the republic, In this regard, the comparison of the lexical system of English and Uzbek languages and the study of the problems of vocabulary in the national-national language interaction, especially in its general typological and comparative-typological aspects, acquires special relevance.